Hubungan Kejadian Postpartum Blues Dengan Motivasi Ibu Dalam Memberikan ASI Pada Bayi 0-12 Bulan Di Puskesmas Tenayan Raya - Fenny, Fenny; Sari, Endah Purwani; Utari, Mona Dewi (JURNAL PENDIDIKAN KESEHATAN, 2024)
Background: Postpartum depression is a mental health problem after giving birth which affects the mother's behavior including breastfeeding the baby. The Carita Health Center's report data shows that cases of postpartum depression in the last three years have fluctuated, namely 2021 (25.34%), 2022 (22.96%) and 2023 (29.01%). Purpose of Writing: Knowing the relationship between postpartum depression and breastfeeding in infants in the Work Area of the Carita Public Health Center, Tenayan Raya. Methods: This study used a quantitative method with a cross sectional design. The sample of this research was postpartum mothers as many as 77 people. The sampling technique used purposive sampling. The research instrument used a questionnaire. Data analysis using univariate and bivariate. Results: Most of the respondents did not breastfeed their babies (51.9%) and experienced postpartum depression (53.2%). There is a relationship between postpartum depression and breastfeeding for babies in the Work Area of the Carita Public Health Center, Tenayan Raya , (p=0.000; OR = 7.091). Conclusions : Postpartum depression has a significant relationship with breastfeeding in infants. It is expected that mothers who are pregnant regularly make ANC visits and take part in class activities for pregnant women so they can get information related to pregnancy, childbirth and postpartum problems from health workers, so as to reduce the risk of health problems both during pregnancy, childbirth and postpartum including the incidence of postpartum depression. partum. To health workers so that they can carry out early screening when mothers make ANC visits and follow up for postpartum women who have symptoms of postpartum depression so that they do not escalate to postpartum depression.